Pendampingan dan Pembinaan Akhlak pada Anak Oppositional Deffiant Disorder pada Madrasah Diniyah Hidayatush Shibyan - Alfa Padlianata; Ahmad Kirom (Social Science Academic, 2025)
This study aims to describe the in children oppositional deffaint disorder in Gundik,Slahung.This research uses the ABCD (Asset Based Community Development) which prioritizes moral development in children who experienceoppositional defiant disorder.The research informants are owners or those who teach at madrasah diniyah,the results of this study are who experience disturbances such as irritability,opposition,likes to be ignorant of their friends.Their behaviour patterns show resistance to the authority of both parents and teachers at school,the solution for handling children who experience this disorder is to provide training to parents,parents make rules that are applied consistently,parents give rewards,and involve all family members with the same perspective.The application of the uswah method (exemplary),practice or habituation,telling stories or fairy tales can reduce symptoms in children oppositional defiant disorder.